Give Progesterone a chance - Labombarda, Maria Florencia (2014)
There is currently no standard pharmacological treatment for spinal cord injury. Here, we suggest that progesterone, a steroid hormone, may be a promising therapeutical candidate as it is already for traumatic brain injury, where it has reached phase II clinical trials. We rely on previous works showing anti-inflammatory, neuroprotective and promyelinating roles for progesterone after spinal cord injury and in our recent paper, in which we demonstrate that progesterone diminishes lesion, preserves white matter integrity and improves locomotor recovery in a clinically relevant model of spinal cord lesion.